Preventive diplomacy is a tool for achieving international peace and security - QUSAI MIJBIL SHANNOUN ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Since the nations existed, the world has witnessed circumstances and situations in which the most basic human rights are violated and the weak person is unable to defend himself. The international community called for the purpose of living in freedom and safety, and the world began to reduce the gaps of wars and international conflicts that do not mean anything through international agreements according to the principle of international security In society, there are many ways that can contribute to maintaining international peace and security, including diplomatic and preventive way to resolve conflicts before they occur, with an explanation of the role of those countries that contributed in this way, to build an international community or regions that solve the conflict befor it occurs with an indication of the Iraqi role in preventive diplomacy and the reasons for its weakness in Iraq .